COVID-19 registration in people with intellectual disabilities in Dutch long-term care facilities. (20th October 2021) - Koks-Leensen, M; Schalk, B; Bakker-van Gijssel, E; Cuypers, M; van den Bemd, M; Nägele, M; Naaldenberg, J; Leusink, GL
Abstract: This study aims to present a nationwide registration of COVID-19 in people with ID living in residential settings, in order to provide insight in COVID-19 epidemiology in this vulnerable group. In a health crisis as the current worldwide COVID-19 pandemic, it is crucial to gain knowledge about the new infectious disease and its effects on health. Identifying risk groups is important for adequate preventative measures and policy-making. People with ID generally have poorer health than others in the general population, with higher prevalence of co-morbidities, risk factors such as obesity, and higher excess mortality rates for infectious diseases. However, there is little reliable knowledge about specific risks and consequences of COVID-19 in the ID population as compared with the general population. To increase this knowledge a nationwide registration system for data on people with ID was set up in Dutch long term care facilities. The registration covered more than 6500 patients with (suspected) Covid-19 infection observed in 2020 and registration is still ongoing. Organizations registered data of their patients with either suspected or confirmed COVID-19 infection, regarding sociodemographics, medical history and COVID-19 infection characteristics. People with ID are vulnerable to COVID-19 at a younger age compared to people in the general population. Case fatality rate was 3-4 times higher among people with ID compared to the general population, and mortality was already higher in younger age groups (40 years and older). Their living circumstances matter: in group home living circumstances more infected people with ID were observed. The etiology of the ID, especially Down syndrome, is an unfavorable predictor. According to these findings, people with ID proved to be vulnerable for COVID-19. Policy makers and care providers should adequately account for this increased vulnerability of the ID population.